Management of Biological Therapy Before Elective Inflammatory Bowel Disease Surgeries. Issue 10 (22nd February 2019) - Hansen, Tawnya M; Targownik, Laura E; Karimuddin, Ahmer; Leung, Yvette
Abstract: Increasing uptake of biologic therapy has contributed to declining surgical rates for inflammatory bowel disease (IBD). However, a significant number of patients on biologic therapy will go on to require surgery. The literature is conflicted with regard to the preoperative management of biologic therapy before urgent or elective IBD surgery. This article reviews the available data on postoperative complications following preoperative treatment with anti-tumor necrosis factor alpha therapy, anti-integrin therapy, and anti-interleukin therapy. Abstract : The literature is conflicted with regard to the preoperative management of biologic therapy prior to IBD surgery. This paper will propose a management strategy and review the current data on postoperative outcomes in IBD patients exposed to biologic therapy.